Second language psychological speaking and listening needs: Scale development, symbiosis, and demographic differences - Xu, Jian; Qiu, Xuyan (Studies in Second Language Learning and Teaching, 2022)
This study aimed to develop and validate two parallel scales to measure the psychological L2 speaking and listening needs of 863 English-as-a-foreign language (EFL) learners. The associations between three psychological needs (i.e., autonomy, competence, and relatedness) of L2 speaking and of L2 listening were examined to develop insights into oracy (i.e., integration of speaking and listening) in L2 communication. Subsequently, the impact of demographic variables was explored. The data, collected via a 5-point Likert-scale questionnaire, were analyzed through descriptive and correlation analysis, factor analysis, and ANOVA. Exploratory factor analysis was conducted to determine the factor structures, followed by confirmatory factor analysis for validation. Results demonstrated that the validity and reliability of the two developed scales were satisfactory. L2 speaking autonomy was significantly related to L2 listening autonomy, as were competence and relatedness. The three psychological needs of both L2 speaking and listening revealed varying patterns in terms of gender, major, university geographical context, schooling stage (first year to fourth year), and study-abroad experiences. The research findings reinforce the need for integration of L2 speaking and L2 listening when satisfying university students’ psychological needs, contribute to the research field with the measurement scales of psychological needs in L2 speaking and listening settings, and yield implications for teaching the two language skills integratedly.